PENGARUH PENGGUNAAN MESIN CNC ROUTER TERHADAP WAKTU STANDAR PENGERJAAN ORNAMEN DESAIN INTERIOR - Adi Nugroho; Sujadi S (JURNAL REKAYASA SISTEM INDUSTRI, 2019)
This study aims to determine the effect of using CNC routers on the standard production time of ornament products at PT Victory Synergy. CNC itself is a machine that is controlled through numeric and letter codes (numerics) which consists of three main components, namely the computer, interface, and actuator system. The research method used in this study is a quantitative approach. Information or research data is obtained through observation, literature studies and interviews with production operators. Based on the results of measurements that have been done, it shows that the existence of CNC routers on the production floor was able to shorten the production stages that were previously carried out to reduce the production cycle time to reach 63.97 minutes or ± 1 hour from the previous production process. This condition also proves that the design of these simple CNC routers can shorten the standard production time that occurs at PT Victory Synergy